WORKING CONDITIONS OF WORKERS IN AREAS OF THE CYLINDER LINER INGOTS PRODUCTION USING ROTARY AUTOMATIC MACHINES - A. M. Lazarenkov; S. A. Horeva; V. A. Kalinichenko (Литьë и металлургия)
Working conditions of workers at the sectors of sleeve-cylinders ingots using rotary automatic machines are examined. Classification of working places of founders of basic professions handling rotary automatic machines at production of sleeve-cylinders ingots is given.